1978
DOI: 10.1203/00006450-197804000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Two-hour Adrenocorticotropic Hormone Test: Accuracy in the Evaluation of the Hypothalamic- Pituitary-Adrenocortical Axis

Abstract: Summary subnormal basal and stimulated levels. Thus the ACTH test didThe inter-and intraindividual variations of response to an iv not diierentiate this state from ACTH deficiency.bolus of tetracosactide (0.25 mgl1.73 m2) were studied, and a definitive diagnostic 2-hr test was established. The test was Speculation given to 179 subjects: hypopituitary, prednisone-treated nephrotics, patients with the autoimmune polyendocrinopathyWhen the Witeria for a in the 2-hr iv ACTH candidinsis syndrome (APECS), and refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Basal and 2-h cortisol levels show no intra-individual dependence and are thus independent measures of cortisol secretory capacity. In contrast, the increment is totally dependent on the intra-individual variations in the basal and 2-h levels; hence, the increment should not be taken as the sole parameter of the test result (13). Surprisingly, we observed subnormal basal cortisol levels in only a few patients with far ., R. …”
Section: Hat In H~vpocortisolism: Apeced Versus Hypopituitarismmentioning
confidence: 38%
See 2 more Smart Citations
“…Basal and 2-h cortisol levels show no intra-individual dependence and are thus independent measures of cortisol secretory capacity. In contrast, the increment is totally dependent on the intra-individual variations in the basal and 2-h levels; hence, the increment should not be taken as the sole parameter of the test result (13). Surprisingly, we observed subnormal basal cortisol levels in only a few patients with far ., R. …”
Section: Hat In H~vpocortisolism: Apeced Versus Hypopituitarismmentioning
confidence: 38%
“…Normal response criteria for the 2hAT were based on results for 30 healthy children aged 2.8-18.4 years. Because both the 2-h plasma cortisol levels and the 2-h increments showed a strong inter-individual dependence on the basal level, a normal result is most accurately defined by an area formed on a plot of 2-h level verslls basal level by the 95% confidence limits for the estimation of 2-h levels for given basal levels, and by the 95% confidence limits for the basal level (7-36 pgJdl; 0.19-1 .OO pM) (13). An increment of ~3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test has been well standardized for clinical use (12). Our data show that the responsiveness of the adrenal cortex at 24 hr of age is not impaired, even if the mother has received twice 12 mg of betamethasone during 24 hr before delivery.…”
Section: Cortisol Studiesmentioning
confidence: 62%
“…In one study a third of normal subjects failed to demonstrate an increase greater than 200 nmol.l ¹1 [47]. Furthermore, the cortisol increment is inversely proportional to the basal cortisol value and hence smaller increases are obtained in the morning when endogenous concentrations are already high [48,49]. It has been suggested that calculation of the incremental increase in serum cortisol has no value [50].…”
Section: The Short Synacthen Test (Sst)mentioning
confidence: 99%